2018
DOI: 10.1186/s12879-018-3540-8
|View full text |Cite
|
Sign up to set email alerts
|

A case of hepatic anisakiasis caused by Pseudoterranova decipiens mimicking metastatic liver cancer

Abstract: BackgroundAnisakid nematodes (Anisakis spp. or Pseudoterranova spp.) usually infect gastric or intestinal walls, while they rarely infect in extra-gastrointestinal sites of human body. Generally, Anisakis spp. larvae are highly infected in fish intermediate hosts, whereas Pseudoterranova spp. larvae are very rarely infected. To the best of our knowledge, there have been no reports which have documented cases of hepatic anisakiasis caused by Pseudoterranova spp. This report describes the first documented case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…Identification of a granuloma in hypaxial muscle, and the presence of the exogenous material inside, suggests that a parasite was encysted and that the immune system was involved in its destruction. The structural elements described in this work are consistent with those reported by Murata et al (2018) for a case of hepatic anisakiasis; however, in this work, elongated bacillary structures were observed in the center of the lesion, suggesting the presence of nematode-like bacteria, such as Flavobacterium spp., Pseudomonas spp., or Bacillus cereus (Svanevik & Lunestad, 2017). The histopathology of the nematode revealed the lateral epidermal cord in the form of a thick "T"; this is probably because the tissue was squashed and the structure changed; however, there is a possibility that the shape of the cord may be related to the parasitic genus, although more studies are needed to test this hypothesis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Identification of a granuloma in hypaxial muscle, and the presence of the exogenous material inside, suggests that a parasite was encysted and that the immune system was involved in its destruction. The structural elements described in this work are consistent with those reported by Murata et al (2018) for a case of hepatic anisakiasis; however, in this work, elongated bacillary structures were observed in the center of the lesion, suggesting the presence of nematode-like bacteria, such as Flavobacterium spp., Pseudomonas spp., or Bacillus cereus (Svanevik & Lunestad, 2017). The histopathology of the nematode revealed the lateral epidermal cord in the form of a thick "T"; this is probably because the tissue was squashed and the structure changed; however, there is a possibility that the shape of the cord may be related to the parasitic genus, although more studies are needed to test this hypothesis.…”
Section: Discussionsupporting
confidence: 90%
“…and butterfly wing shape for Pseudoterranova spp. (Lauwers et al, 2017); the specification of this structure in human medicine has been reported for hepatic anisakiasis due to Pseudoterranova decipiens (Murata et al, 2018), A. pegreffii, and A. simplex in cases of dysentery (Amir et al, 2016). In fish, only Laffon-Leal et al (2000) reported the genus Contracaecum spp.…”
Section: Discussionmentioning
confidence: 99%
“…Anisakids are responsible for a relatively poorly known food-borne zoonosis named anisakiasis or anisakidosis that results from the accidental ingestion of marine products harboring infective L3 in the edible parts. The pathology shows mild-to-severe gastrointestinal and/or allergic symptoms and clinical signs, such as rhinitis, urticaria, and anaphylactic shock [ 3 ], and there is increasing evidence that suggests the occurrence of tumors in the same localization of larvae [ 4 , 5 , 6 ]. For these reasons, the need to fill the gap in knowledge about the pathogenetic mechanisms of such parasitic disease appears clear.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of nematodes of the Anisakidae family is worldwide, and their identification through molecular tests has been carried out more frequently in the Asian continent [ 115 ], where the consumption of fish is higher, registering a per capita consumption of 24.1 kg/year [ 12 ], which is consistent with the Asian diet, which is based mainly on the consumption of raw and semi-raw seaFood In a study by Yokogawa and Yoshimura [ 116 ], they reported parasitic infestation by Anisakis spp. in Japanese patients with clinical symptoms affecting the gastrointestinal tract, using the term “larval anisakiasis” to determine that the disease was caused by a parasite of the Anisakidae family through the consumption of raw fish and squid.…”
Section: Geographical Distributionmentioning
confidence: 99%
“…Encystment has also been observed in the intestinal epithelium that can trigger the presentation of cancer; however, this will depend on the mutagenicity of the cells and the tumor-promoting potential of larval antigens [ 145 ]. In a study carried out by Murata et al [ 115 ], a case of hepatic anisakidosis caused by P . decipiens was reported, which was first diagnosed in the patient as a neoplasm; however, when analyzing the tumor, it was identified that it was an eosinophilic granuloma, in which the larva was located at the center of the lesion.…”
Section: Anisakiosis/anisakiasismentioning
confidence: 99%